Recent Advances in Meerwein Arylation Chemistry - Kindt, Stephanie; Heinrich, Markus (Synthesis (Germany), 2016)
The Meerwein arylation has recently received much attention and a variety of new variants have been developed. Advances include new sources for aryl radicals, new radical scavengers, as well as improved reaction conditions. This short review summarizes important developments that make this radical-type reaction an even more powerful tool for the diverse functionalization of alkenes. 1 Introduction 2 Meerwein Arylations 2.1 Carboarylation 2.2 Carboamination 2.3 Carbooxygenation 2.4 Carbothiolation 2.5 Carbofluorination 3 Summary.
Keywords: alkene; diazonium; Meerwein arylation; photocatalysis; radical reactions; radical-polar crossover